2022
DOI: 10.1097/md.0000000000032002
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological pulmonary findings of survivors and autopsy COVID-19 cases: A bi-center study

Abstract: The coronavirus disease 2019 (COVID-19), caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2), evolved into a global pandemic. As ACE2 on the surface of alveolar cells of the lung epithelium is one of the potential target receptors for SARS-CoV-2, the respiratory symptoms are the most common presentation of COVID-19. The aim of our study was to investigate the morphological findings in lung tissue after being infected by SARS-CoV-2 and compare histopathologic changes in patients with COVID-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 51 publications
(143 reference statements)
0
4
0
Order By: Relevance
“…26 Pleural and peribronchial fibrosis were also more evident in our SARS-CoV-2 (+) LT patients with pneumonia; the same lesions have also been described in a few case series. 11,12,25,31 Only two studies reported a similar experience: evaluation of lung samples distant from neoplasia. 11,25 Nevertheless, these are descriptive and anecdotic case series, and the results are inconclusive.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…26 Pleural and peribronchial fibrosis were also more evident in our SARS-CoV-2 (+) LT patients with pneumonia; the same lesions have also been described in a few case series. 11,12,25,31 Only two studies reported a similar experience: evaluation of lung samples distant from neoplasia. 11,25 Nevertheless, these are descriptive and anecdotic case series, and the results are inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…11,12,25,31 Only two studies reported a similar experience: evaluation of lung samples distant from neoplasia. 11,25 Nevertheless, these are descriptive and anecdotic case series, and the results are inconclusive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations